A comparative study of pharmaceutical institutions in Iran and abroad - Cheraghi, Yasaman; Bagheri Alamooti, Azar; Sabet Eghlidi, Nazanin; Shahisavandi, Mina; Mostafavipoor, Seyed Mehrdad; Niknahad, Hossein (International Pharmacy Acta, 2018)
Introduction: In different countries, various organizations and associations are active in the field of pharmacy. These activities mainly consist of policy-making, implementation, training and supervision. In Iran, different tasks are concentrated in one or two institutions; and the active presence of the private sector is not tangible. On the other hand, in developed countries, tasks are divided between public and private institutions. In this article, by investigating and comparing these institutions in different countries and drawing conclusions, systems for dividing tasks with greater efficiency will be achieved. Methods and Results: The workgroup on "Investigating Pharmaceutical Institutions" of Pharmaceutical-Strategic-Studies-Office conducted a study on the responsibilities of each of these institutions, their target population, efficiency rate on the defined objectives in policy, implementation, monitoring and education areas in Iran, neighboring countries and developed countries, as well as their different and similar duties with each other. In this review article, several searches have been done in databases such as PubMed, Google Scholar, Scopus, specialized books as well as websites related to each of these institutions. The results show that in developed countries an average of six pharmaceutical associations exist, all of which are active in the field of education. In the United States, an organization that approves the competency of pharmacists and issues pharmacy establishment permits has been separated from overseeing organizations. In Japan, other than the Health Ministry as a policy-maker and a special council for legislative purposes, a formal overseeing institution, an Office of Health Assessment and two associations with a scientific-trade and research approach are active. In Australia, one third of the associations are active in the area of law enforcement; and the organization which is active in the field of policy-making and supervision does not have any executive activities. In the European Union, one institution has a role in the field of macro policy-making and two associations are involved in micro policy-making. In India and Pakistan, practically all affairs are carried out in the governmental format; NGOs operate in the field of education, research and government consultation. Overall, China is the most similar to Iran.